Synthesis and characterization of Schiff base liquid crystals with benzothiazole ring - Kew, Ho Yang (2025)
A series of benzothiazole ring Schiff base ether liquid crystals (E)-1-(4- (alkyloxy)phenyl)-N-(6-methoxybenzo[d]thiazol-2-yl)methanimine, BRLCn (CnH2n+1O-, where n = 12, 14, 16, and 18) were successfully synthesized, characterized and the mesomorphic properties were investigated. Two major steps were involved for synthesis. The first step is the Schiff base condensation between 2-amino-6-methoxy benzothiazole and 4- hydrobenzaldehyde with the aid of glacial acetic acid formed imine linkage (C=N) between two aromatic benzene rings. The second step is the formation of ether linkage, BRLCn through the etherification between BMB1 and bromoalkane. The molecular structures of the synthesized compounds were determined using Fourier Transform (FTIR), 1D NMR (1H and 13C) and 2D NMR (COSY, HMBC, and HMQC). The mesomorphic properties of synthesized compounds were identified using Differential Scanning Calorimetry (DSC) as well as the photophysical properties using UV-Vis spectroscopy. All the compounds BRLCn (where n = 12, 14, 16, and 18) exhibit two liquid crystal phases.